Strategic motives, proactive environmental strategies and corporate performance: Role of business model innovation and competitive intensity - Kamran Ali; Muhammad Amir; Muhammad Siddique Malik (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2023)
Rapidly increasing environmental concerns drive corporations to enhance their performance through measures designed to make environmental activities appealing to stakeholders. Therefore, this study investigates the influence of strategic and regulationbased motives on corporate performance and explores the mediating role of proactive environmental strategies, along with the moderating effects of business model innovation and competitive intensity. Quantitative data from the Pakistani manufacturing sector is gathered through a self-administered survey, and the hypotheses are tested using PLS-SEM with SmartPLS 4. The findings indicate that strategic motives indirectly impact corporate performance by adopting PES. Furthermore, the results reveal that business model innovation and competitive intensity influence the relationship between strategic motives and PES. This study has significant implications for managers actively seeking ways to enhance their corporates' performance through proactive environmental strategies. Moreover, policymakers can use these findings to inform the design of policies promoting environmental protection. This study contributes to the Natural Resource-based View (NRBV) and highlights the critical role of PES in enabling corporates to enhance their appeal to stakeholders and ultimately improve their performance.
Keywords: 330; Strategic motives; proactive environmental strategy; corporate performance; business model innovation; competitive intensity; manufacturing sector; Pakistan